Numerical and experimental study of high-temperature multi-cycle fatigue strength of single-crystal gas turbine blades - Yevhen Nemanezhyn (Авіаційно-космічна техніка та технологія)
The subject of the research is anisotropic single-crystal turbine blades of aircraft gas turbine engines (AGTE), as well as their multi-cycle fatigue strength characteristics at high temperatures. The goal of this study was to determine the endurance limit of single-crystal high-pressure turbine blades of an AGTE at high temperatures of 820°C. The objective of the study is to develop a method for calculating and experimentally investigating the characteristics of high-temperature multi-cycle fatigue strength of gas turbine blades made of single-crystal nickel heat-resistant alloys. The research methods used are: method of computer modelling, which was used to create a 3D model of a cooled high-pressure turbine blade; finite element method, which was used to determine the stress-strain state of the blade according to the selected form of resonant vibrations; strain and resonance methods, which were used to determine the fatigue strength characteristics of single-crystal turbine blades under high-temperature loading. The following results were obtained. Literary sources describing theoretical and experimental methods for determining the strength characteristics of blades under combined dynamic and high-temperature loading were analyzed. The developed special installation for testing turbine blades under conditions of temperature and dynamic (resonant) loading was described. A combined method for assessing the multi-cycle fatigue strength at high temperatures is proposed, which includes studies on full-scale turbine blades and finite element calculations. The dynamic and temperature characterization of single-crystal turbine blades selected for the study was carried out and described. Fatigue tests were performed to determine the endurance limit of the blades at a high temperature equal to  T = 820 °C. Conclusions. The scientific novelty of the obtained results is as follows. A specialized experimental setup was developed to study the endurance limit of single-crystal AGTE blades under high-temperature loading. A method for combining numerical (ANSYS) and experimental (field tests) study of high-temperature multi-cycle fatigue strength of turbine blades made of single-crystal heat-resistant alloys was developed. The direction of further research is presented.